PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, AGENCY COST, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Nur Vikha Alifia (2023)
This research is a quantitative study that aims to analyze the effect of corporate social responsibility disclosure, agency costs, and dividend policy on firm value. The dependent variable, firm value, is measured using Tobin's Q. The independent variable corporate social responsibility disclosure is measured using the GRI standards, agency cost is measured using the expense ratio, and dividend policy is measured using the dividend payout ratio. This study uses company size as a control variable as measured by the natural logarithm of company assets. The data used in this study is secondary data and the samples in this study were selected through a purposive sampling method from manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange from 2019 to 2021. The total sample obtained is 74 companies which are unbalanced data. Hypothesis testing and statistical analysis used STATA version 13. The results of the study found that disclosure of corporate social responsibility have a positive and significant effect on firm value while agency costs and dividend policy do not have a significant effect on firm value.